Application of several advanced oxidation processes for degradation of 4-chlorophenol from aqueous solution - Abdolmotaleb Seid Mohammadi; Ghorban Asgari; Afshin Ebrahimi; Hossein Movahedian Attar; Zahra Sharifi (International Journal of Environmental Health Engineering, 2013)
Aims: In this work, degradation of 4-chlorophenol (4-CP) was investigated in aqueous solutions using several oxidation systems involving ultraviolet/(UV)/H 2 O 2 , microwave (MW)/H 2 O 2 , and ultrasonic (US)/Fenton systems. Materials and Methods: Three pilot plant reactors consist of a photolytic reactor, a modified domestic MW, and an US bath reactor of 22 kHz frequency were constructed and separately used in batch mode. The effects of several operation parameters such as pH of the solution ranging 3-10, H 2 O 2 initial concentration ranging from 0.005 to 0.2 mol/l, and reaction time were examined. Concentration changes of 4-CP were determined using a spectrophotometer at an absorption wavelength of 500 nm. Results: The results show that the oxidation rate was influenced by many factors, such as the pH value, reaction times, and the amount of H 2 O 2 concentration. The optimum conditions obtained for the best degradation rate were pH = 7, H 2 O 2 concentration of about 0.05 mol/l and pH = 10, H 2 O 2 concentration of about 0.1 mol/l for UV/H 2 O 2 and MW/H 2 O 2 system, respectively. For US/Fenton system, the highest 4-CP degradation was achieved in pH = 3, H 2 O 2 concentration of about 0.05 mol/l in the percent of 0.025 mmol Fe/l. The highest 4-CP removal rate in optimum conditions of pH and concentration of H 2 O 2 , in UV/H 2 O 2 , MW/H 2 O 2 , and US/Fenton systems was >99% over the retention time of 40 min, 85% after 180 min, and >99% after 40 min, respectively. Conclusion: Based on the results of this study, the UV/H 2 O 2 and US/H 2 O 2 are successfully applicable for degradation of 4-CP in aqueous solution. Also, the kinetic study represented that the US/H 2 O 2 is capable of removing 4-CP slightly rather than UV/H 2 O 2 process.